Aeronautical and Space Engineers from the Eyes of Sixth Grade Students - (:unkn) unknown (DERGIPARK AKAD, 2019)
The purpose of this study is to identify middle-school students' perception of aeronautical and space engineers. The study group of the study which is a descriptive survey model consists of 50 6th grade middle-school students located in the Adilcevaz District of Bitlis Province. In the study, a drawing form and the 'Who are Aeronautical and Space Engineers?' form have been used as data collection tools. In the analysis of data, content analysis and descriptive analysis have been used. As a result of the study, it has been determined that a majority of the students had misconceptions about what aeronautical and space engineers do. In addition, it has been concluded that the students have a stereotypical gender perception about engineers. In the light of these findings, the importance of introducing different engineering areas such as aeronautical and space engineering to the students in forming a career awareness about engineering and the inclusion of the applications in these areas in educational environments has been underlined.
Keywords: aeronautical and space engineers; STEM education; career; 6th grade students; stereotypical gender perception; EDUCATION